Trinity Education Project Interim Report - Prendergast, Patrick; Hogan, Linda (Trinity College Dublin , the University of Dublin, 2016)
Goal 3 of the Strategic Plan 2014–19 is focused on the renewal of the Trinity Education, and particularly on the renewal of the undergraduate curriculum. It begins with the acknowledgment of the strengths of our current programmes, noting in particular that the Trinity education is rooted in a curriculum inspired by current research and scholarship, taught by academics with international reputations in their respective fields, who work together with professional staff to harness the excellence and diversity of the multidisciplinary university. It notes, however, that the curriculum must continue to evolve in light of new discoveries in disciplinary knowledge, pedagogy, and also in the recognition that the context in which our graduates participate is ever-changing.